Pan-genome analysis of Alistipes Genomes: Exploration of diversity and pathogenicity - Nath Tonmoy, Joy Deb (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.